Trimethylsilyl azide (C3H9N3Si): a highly efficient additive for tailoring fluoroethylene carbonate (FEC) based electrolytes for Li-metal batteries. Issue 22 (21st May 2019) - Park, Seong-Jin; Hwang, Jang-Yeon; Sun, Yang-Kook
Abstract : The addition of trimethylsilyl azide (C3 H9 N3 Si) to FEC-based electrolytes enhances Li-metal stability and thus it enables the outstanding cycling stability of Li-metal battery at a practical level. Abstract : In this study, trimethylsilyl azide (C3 H9 N3 Si, hereafter denoted as TSA) is used as an efficient electrolyte additive in Li-metal batteries. Along with a LiF-rich compound, the addition of 0.1 M TSA to fluoroethylene carbonate (FEC)-based electrolytes not only induces the formation of a conductive solid-electrolyte interphase layer on the Li-metal surface but also allows the formation of a dense Li-deposit morphology; hence, it greatly enhances the Li plating–stripping reaction kinetics. Upon using the 0.1 M TSA additive, a practical Li/full concentration gradient Li[Ni0.73 Co0.10 Mn0.15 Al0.02 ]O2 (FCG73) battery exhibits outstanding long-term cycling stability over 300 cycles and fast charge–discharge capability at a practical level.